Pendampingan dan Optimalisasi Daya Saing UMKM Menggunakan E-Catalog di Kelurahan Gedog Kota Blitar - Rizky Ramadhani; Rahman Amrullah Suwaidi (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
UMKM must be able to face global challenges, increase product and service innovation. UMKM are the economic sector that absorbs the largest workforce in Indonesia. Gedog Village needs technology in the midst of globalization. Most of the problems faced are product marketing and their lack of human resource knowledge. The Thematic 31 KKN group aims to take part in imparting the knowledge that we have to impart to them so that the business being run can develop so that the coffers of income will increase and be able to recruit new workers. Assistance to the UMKM sector in Gedog Village needs to be given socialization about what to do and provide examples of action. In the data collection process, three methods were carried out, namely interviews, document studies, and questionnaires.